Analisa Kepuasan Pengguna Web dengan Partial Least Squares-Structural Equation Modeling Berbasis WebQual 4.0 (Dinas Lingkungan Hidup Kota Pekalongan) - Krisna, Muhammad Donny Sri Adhi; Santoso, Dwi Budi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The study's goal is to analyze and evaluate user satisfaction with the Pekalongan City Environmental Agency website utilizing the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach based on WebQual 4.0. This study looks at three main aspects of WebQual 4.0 Usability(ease of navigation, user-friendly design), Information Quality (accuracy, relevance, timeliness), and Service Interaction (customer support, responsiveness, personalization), to identify the most influential factors on user satisfaction. Data was collected through an online survey targeting active users of the website. Utilizing PLS-SEM, the statistical significance of the correlations between these variables and user satisfaction was examined, and path coefficients were computed. The findings indicate that all three WebQual dimensions significantly influence user satisfaction. Service Interaction was identified as the most dominant factor with a very strong positive influence, followed by Usability and Information Quality. This analysis provides insights for website administrators to develop strategies aimed at enhancing user satisfaction. By focusing on improving service interaction and usability, as well as ensuring the delivery of high-quality information, the Pekalongan City Environmental Agency's website can be more effective in meeting the public's information and service needs..